2019
DOI: 10.2176/nmc.oa.2019-0133
|View full text |Cite
|
Sign up to set email alerts
|

The Tight Medial and High Convexity Subarachnoid Spaces Is the First Finding of Idiopathic Normal Pressure Hydrocephalus at the Preclinical Stage

Abstract: Disproportionately enlarged subarachnoid-space hydrocephalus (DESH) findings are often reported as characteristic radiological features of idiopathic normal pressure hydrocephalus (iNPH). However, the process of development of DESH remains unclear. The aim of the present study was to determine the dynamic deforming process and pathophysiology of iNPH. All patients >50 years of age who underwent whole body FDG-PET/CT scanning at Kindai University Hospital between May 2017 and April 2018 were included in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…To our knowledge, this is the first report assessing the changes in regional cerebral glucose metabolism using FDG-PET/CT in the prodromal stage of iNPH. We previously reported that iNPH develops in the order of PMD, AVIM, and iNPH [13], with PMD (asymptomatic incomplete DESH) progressing to AVIM (asymptomatic complete DESH), which processes to iNPH (symptomatic complete DESH). In this study, we also evaluated cerebral glucose metabolism during the progression of iNPH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, this is the first report assessing the changes in regional cerebral glucose metabolism using FDG-PET/CT in the prodromal stage of iNPH. We previously reported that iNPH develops in the order of PMD, AVIM, and iNPH [13], with PMD (asymptomatic incomplete DESH) progressing to AVIM (asymptomatic complete DESH), which processes to iNPH (symptomatic complete DESH). In this study, we also evaluated cerebral glucose metabolism during the progression of iNPH.…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively reviewed the medical records for brain images and clinical features of all 2196 patients, who are > 50 years of age and who underwent a whole body FDG-PET/CT scanning at Kindai University Hospital between May 1, 2017 and April 31, 2018 [13]. There were 79 cases with preclinical or clinical iNPH from this cohort (based on brain morphologic features of iNPH), and they were enrolled in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations